2016
DOI: 10.1016/j.biortech.2016.08.073
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of process parameters for production of volatile fatty acid, biohydrogen and methane from anaerobic digestion

Abstract: The anaerobic digestion process has been primarily utilized for methane containing biogas production over the past few years. However, the digestion process could also be optimized for producing volatile fatty acids (VFAs) and biohydrogen. This is the first review article that combines the optimization approaches for all three possible products from the anaerobic digestion. In this review study, the types and configurations of the bioreactor are discussed for each type of product. This is followed by a review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
104
0
12

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 263 publications
(126 citation statements)
references
References 97 publications
(68 reference statements)
1
104
0
12
Order By: Relevance
“…Higher organic overload is reported to cause a destabilization in the AD by exceeding the hydrolytic capacity of the bacteria community, resulting in a reduction of methane production . Moreover, this imbalance is connected to the accumulation of VFAs because it involves higher acidogenesis rates and pH drops . In this sense, one promising strategy to accumulate VFAs, would be to increase the substrate to inoculum ratio.…”
Section: Resultsmentioning
confidence: 99%
“…Higher organic overload is reported to cause a destabilization in the AD by exceeding the hydrolytic capacity of the bacteria community, resulting in a reduction of methane production . Moreover, this imbalance is connected to the accumulation of VFAs because it involves higher acidogenesis rates and pH drops . In this sense, one promising strategy to accumulate VFAs, would be to increase the substrate to inoculum ratio.…”
Section: Resultsmentioning
confidence: 99%
“…The highest concentration of organic acids were an acetic acid which was observed in both dairy cattle waste (sludge biogas, fresh feces) and cattle, biogas sludge, fresh feces, rumen content). It was reported that the acetate was the precursor of approximately two-thirds of the methane produced in mesophilic (30-40°C) and thermophilic (45-65°C) [14,15]. The volatile fatty acids are converted into biogas precursors by acetogenic bacteria during the formation of biogas (the acetogenesis stage), i.e.…”
Section: Resultsmentioning
confidence: 99%
“…The main factor affecting the methane production is an accumulation of volatile fatty acids (VFAs) concentration in the reactor produced during the acidogenesis step. VFAs is a precursor for the production of biopolymers (PHA), biofuels, alcohols, aldehydes or ketones [14][15][16]. Therefore, the balance can be difficult to manage on a large scale production because acidogens and acetogens continuously produce compounds that reduce the pH of the system below the preferred range of 6.4-8 for methanogens if sufficient buffering capacity is not available.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the direct water splitting via the semi‐conductive photocatalyst that has attracted many interests in the past, the bio‐hydrogen process still remains competitive because of its many appealing advantages, ie, cost‐effectiveness, simplicity in operations, independence of solar radiation, and highly efficient utilization of renewable lignocellulose . Although efforts of investigating dark hydrogen fermentation have been made for a few decades, there are still quite many spaces left for the optimization of the entire process in the aspect of maximizing the hydrogen yield, minimizing the secondary metabolites inhabitations, and maintaining the stability of the microbes during fermentation . In order to enhance the hydrogen yield, different efforts have been trialed by many scholars.…”
Section: Introductionmentioning
confidence: 99%